Phacoemulsification at High-Altitude Himalayan Region: Comparison. Issue 2 (March 2016) - Parihar, Jitendra Kumar Singh; Chaturvedi, Piyush; Kaushik, Jaya; Jain, Vaibhav Kumar; Mukherjee, Shantanu; Mishra, Sanjay Kumar
Purpose: To compare phacoemulsification parameters at different high-altitude regions as well as between peristaltic and Venturi-based machines. Methods: In this prospective, nonrandomized clinical study, 160 eyes of 160 patients with senile cataract underwent phacoemulsification using either peristaltic or Venturi system at a high-altitude Himalayan region (>10, 000 feet). Patients (n = 200, including 100 each with either peristaltic or Venturi system) operated at mean altitude of 1115 feet (Delhi) were included as controls (group 1). At Leh (11, 203 feet), 110 patients were operated with peristaltic (62) or Venturi (48) system (group 2), whereas 50 patients (group 3) (peristaltic = 37; Venturi = 13) were operated either with peristaltic (37) or Venturi (13) system at Tangtse (14, 106 feet). Intraoperative parameters–i.e., bottle height (BH), vacuum (V), and flow rate (FR)–were compared for different phacoemulsification steps–i.e., central chopping (CC), segment removal (SR), epinucleus removal (ER), and cortex removal (CR)–between all groups and between peristaltic and Venturi pump-based machines in each group. Results: Mean BH, V, and FR for CC, SR, ER, and CR significantly increased with the increment in altitude of surgery (p = 0.000). Venturi and peristaltic-based phacoemulsification showed higher values of the mean BH and V, respectively, for CC, SR, ER, and CR at Leh as well as Tangtse. Conclusions: At the high-altitude region, the higher setting of BH, FR, and V is required in phacoemulsification.